2009
DOI: 10.1128/mmbr.00040-08
|View full text |Cite
|
Sign up to set email alerts
|

Tumultuous Relationship between the Human Immunodeficiency Virus Type 1 Viral Infectivity Factor (Vif) and the Human APOBEC-3G and APOBEC-3F Restriction Factors

Abstract: SUMMARY The viral infectivity factor (Vif) is dispensable for human immunodeficiency virus type 1 (HIV-1) replication in so-called permissive cells but is required for replication in nonpermissive cell lines and for pathogenesis. Virions produced in the absence of Vif have an aberrant morphology and an unstable core and are unable to complete reverse transcription. Recent studies demonstrated that human APOBEC-3G (hA3G) and APOBEC-3F (hA3F), which are selectively expressed in nonpermissive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 272 publications
(414 reference statements)
0
73
0
3
Order By: Relevance
“…As Vif expression was increased, the steady state levels of intracellular WT A3G were decreased (Cell, lanes 2-6), while the levels of S-A3G protein were not affected (Cell, lanes [8][9][10][11][12]. Concomitant with the decrease in protein levels of intracellular WT A3G, its incorporation into virions was also reduced (Virus, lanes 2-6), while under identical experimental conditions, S-A3G packaging was not significantly affected (Virus, lanes [8][9][10][11][12]). These findings demonstrate that S-A3G incorporation into HIV-1 virions is independent of Vif.…”
Section: Resultsmentioning
confidence: 99%
“…As Vif expression was increased, the steady state levels of intracellular WT A3G were decreased (Cell, lanes 2-6), while the levels of S-A3G protein were not affected (Cell, lanes [8][9][10][11][12]. Concomitant with the decrease in protein levels of intracellular WT A3G, its incorporation into virions was also reduced (Virus, lanes 2-6), while under identical experimental conditions, S-A3G packaging was not significantly affected (Virus, lanes [8][9][10][11][12]). These findings demonstrate that S-A3G incorporation into HIV-1 virions is independent of Vif.…”
Section: Resultsmentioning
confidence: 99%
“…130 Recent studies revealed that Vif counteracts the human restriction factors APOBEC-3G (hA3G) and APOBEC-3F (hA3F) that have strong anti-HIV-1 activity. APOBEC3G is incorporated in HIV-1 virions 131 in an NC dependent manner.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Les deux publications parues dans Nature [4,5] démontrent que CBF- fait partie du complexe E3 ubiquitine ligase comprenant la Cul-5, Rbx2, Elo-C et Elo-B. Cependant, la fixation de CBF- à ce complexe requiert Vif, ce qui indique que CBF- n'est pas un constituant [2][3][4][5][6]. Quels sont les facteurs présents dans le sperme responsables de cet effet ?…”
Section: Cbf-b : Un Nouveau Ligand De Vif Impliqué Dans L'infectiositunclassified
“…Plusieurs facteurs de restriction inhibant la réplication des rétrovirus, dont les virus de l'immunodéficience humaine de types 1 et 2 (VIH-1, VIH-2), ont ainsi été identifiés : TRIM5 (tripartite motif-containing protein 5), la téthérine, SAMHD1 (SAM domain and HD domain 1), et plusieurs membres de la famille des cytidines désaminases APOBEC-3 (apolipoprotein B mRNAediting, enzyme-catalytic, polypeptide-like 3) [1][2][3]. Parmi ces derniers, A-3G et A-3F, qui sont exprimés dans les cellules cibles naturelles des VIH-1 et VIH-2, sont les plus importants [1,3]. Les rétrovirus ont cependant acquis la capacité de contourner ces facteurs de restriction.…”
unclassified
See 1 more Smart Citation